Estrogen-Related Receptors in Breast Cancer and Prostate Cancer - Misawa, Aya; Inoue, Satoshi (Frontiers in Endocrinology, 2015)
Estrogen signaling pathways are implicated in the development of breast cancer and prostate cancer. Various studies have focused on additional signaling pathways, mediated by estrogen-related receptors (ERRs). ERRs are constitutively active receptors that share a high degree of homology with the classical estrogen receptors (ERs). However, they do not bind to estrogen, while ERs do. ERRs are involved in the development of alternative pathways that lead to the development of cancer and are regarded as potential therapeutic targets for the treatment of breast cancer and prostate cancer that do not respond to conventional therapies. In this review we first present general structural features of ERRs. Then, we focus on breast cancer and prostate cancer, which are primarily hormone-dependent cancers, and summarizes recent progress in elucidating the involvement of each ERR in these two types of malignancies.